Towards sustainable energy futures: multi-objective policy framework for integrating high penetration of renewable energy sources into energy systems - Farnam Dehghani; Mohammad Agha Shafiyi (Sustainable Futures)
Integrating renewable energy is crucial for addressing climate change, environmental issues, and the need for sustainable development. As the demand for cleaner energy increases, innovative approaches are essential to enhance the efficiency and flexibility of energy systems. This paper proposes advanced techniques to increase system flexibility and cut costs, including the economic complementarity of renewable energy sources, sector coupling, and clean technologies such as green desalination, power-to-gas (P2G), and heat recovery solutions. Furthermore, this paper explores the role of private investors in hybrid renewable energy integration. In this context, private investors present new challenges for policymakers, who must balance attracting investors with incentive policies and minimizing total system costs. To handle this, a mixed-integer nonlinear mathematical model is proposed, utilizing the Pareto Front decision-making approach to solve the multi-objective problem. The simulation results reveal that by choosing an appropriate feed-in tariff (FIT) rate and strategically allocating investment permissions to private investors based on economic complementarity, policymakers can lower energy system planning costs by over 100 million USD per year. In addition, the results prove that investments in this sector can reduce CO2 emissions by up to 2.5 million tons and create up to 3400 jobs directly and indirectly. These findings offer practical implications for improving energy policy and aligning with sustainable development goals.